Understanding physical concepts using an immersive virtual learning environment - Pirker, J.; Berger, S.; Guetl, Christian; Belcher, J.; Bailey, P. (Universidad Carlos III de Madrid, 2012)
Understanding basic physical concepts is not an easy task. The Technology Enabled Active Learning Approach (TEAL) is an innovative learning approach and successfully improves the conceptual understanding in teaching freshmen physics at the Massachusetts Institute of Technology. This approach requires specially designed classrooms, hands-on experiments, different teaching methods and also virtual visualizations and simulations to enhance the student's engagement and learning success. The Java-based open-source framework TEALsim was especially designed to support the students understanding of different physical procedures using visualizations and simulations of physical concepts such as Faraday's Law. But not every institution or university is able to use the TEAL scenario because of the high expense in terms of required equipment. Also the distance learning idea is lost. Existing learning spaces are limited regarding time and space. Depending on the learning scope and application domain conventional E-Iearning tools are not always the best choice. Especially such abstract domains as physics are hard to teach without advanced tools. Drawbacks such as the lack of immersion and the lack of communication and collaboration possibilities suggest the introduction of a new e-learning tool, the Virtual 3D World. This paper focuses on the technical aspects of the implementation of TEAsim in the Virtual 3D World Environment Open Wonderland. This collaboration between the CECI at MIT and AEMT group at TU-Graz introduces a first potential scenario of in-world physics simulations. The Open Wonderland solution in particular supports collaborative learning settings, and enables students to have pedagogical valuable discussions about the material being learned.